A Mendelian randomization study on the role of serum parathyroid hormone and 25-hydroxyvitamin D in osteoarthritis. Issue 9 (September 2021) - Qu, Z.; Yang, F.; Yan, Y.; Huang, J.; Zhao, J.; Hong, J.; Li, S.; Jiang, G.; Wang, W.; Yan, S.
Summary: Objective: Serum parathyroid hormone (PTH) and 25-hydroxyvitamin D [25(OH)D] have been demonstrated to be associated with pathogenesis and progression of osteoarthritis (OA). This study aimed to determine the potential causal relationship between serum PTH and 25(OH)D levels and risk of OA. Design: We applied the two-sample Mendelian randomization (MR) approach to estimate the causal roles of serum PTH and 25(OH)D on OA. The instrumental variables for serum PTH and 25(OH)D were derived from two large genome-wide association studies (GWAS), which included 29, 155 and 79, 366 individuals, respectively. Summary-level data for overall, hip and knee OA were extracted from a GWAS meta-analysis, including 455, 221 individuals. All participants included in this study were from the European population. Results: An inverse association was observed between serum PTH levels and risk of OA (random-effects: Effect = 0.71; 95% CI: 0.54 to 0.92; fixed-effects: Effect = 0.71; 95% CI: 0.61 to 0.82). Stratified by site, serum PTH levels were found to be inversely associated with knee OA (random-effects: Effect = 0.53; 95% CI: 0.41 to 0.68; fixed-effects: Effect = 0.53; 95% CI: 0.41 to 0.68). However, there was no evidence of the causal effect of serum 25(OH)D levels on OA. Conclusions: The present study indicates an inverse causal relationship between serum PTH concentrations and development of OA. Moreover, a site-specific association was also observed between serum PTH levels and knee OA. The potential mechanisms by which serum PTH affects OA need to be further investigated.